THROMBOTIC THROMBOCYTOPENIC PURPURA AFTER VACCINATION AGAINST COVID-19 – A CASE REPORT - PANCHAL, YASH N; M PATEL, MAITRI; V PATEL, MUKUNDKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Thrombotic thrombocytopenic purpura (TTP) is a rare but fatal thrombotic microangiopathy. Circulating AntiADAMTS13 antibodies produced in response to various triggering events, such as vaccinations, autoimmune disorders, malignancy, and administration of several drugs lead to acquired TTP (aTTP). This case concerns a 26-year-old male with aTTP after receiving the second dose of the Covishield vaccine (Oxford-AstraZeneca COVID-19 vaccine, code-named AZD1222). He presented with bruises, petechia, fatigue, dyspnea, and arthralgia post-vaccination. Laboratory reports showed thrombocytopenia, hemolytic anemia, a significant ADAMTS13 deficiency, and a high level of autoantibody titer against ADAMTS13. We treated the patient with plasma exchange therapy and prednisolone, and after the treatment, he recovered.